Jiuding capital : private equity firm with Chinese characteristics (B) - Meng, Fei; Jia, Ning; Tian, Xuan ([London] : SAGE, 2016)
On April 23, 2014, Beijing Tongchuang Jiuding Investment Management Co., Ltd. (hereinafter "JD Capital"), the parent company of Jiuding Investment Management Co., Ltd., was listed on China's share transfer system (also known as the New OTC Board or New Third Board; JD Capital's stock code is 430719). It was the first private equity (PE) firm in China to become publicly traded. JD Capital's net assets reached 3.64 billion RMB upon completion of this issuance. Established in 2007, JD Capital had been able to quickly gain a strong foothold in China's private equity market by massively investing in pre-IPO deals and taking advantage of the high valuation offered by the ChiNext Board. JD Capital engaged in a 'factory-style' operational model. This case study discusses this topic.
Originally Published in: Meng, F., Jia, N., & Tian, X. (2015). Jiuding Capital: Private Equity Firm with Chinese Characteristics (B). 4-215-322. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Jiuding Capital (Firm); Investment banking -- Case studies; Venture capital -- Case studies; Strategic planning -- Case studies; Private equity -- China -- Case studies